MOTIVATION AND LEARNING STYLE REFLECTIVE-CRITICAL IN THE UNIVERSIDAD NACIONAL DE INGENIERÍA - Romero Centeno, Romulo (2014)
This investigation had as a fundamental aim to establish the relationship between the intrinsic motivation and the learning style reflective-critical of the students from the Universidad Nacional de Ingeniería during the academic year 2009 II. The study sample was consisted of 371 college students, male and female, economically disadvantaged middle and lower middle regular academic status whose ages range from 16 to 32 years, and also students from the different faculties of the Universidad Nacional de Ingeniería. The sample was selected in a probabilistic way by simple random process. The research design adopted was the correlation to establish the relationship between intrinsic motivation and learning style reflective-critical engineering students. The intrinsic motivation test was used to identify the level of the intrinsic motivation of the students while the level of development of the style-critical reflective learning was measured by a questionnaire of critical reflective learning styles. The results show that (1) the level of intrinsic motivation achieved by university students of different faculties of the Universidad Nacional de Ingeniería is located in the high and medium level. (2) The level of development of reflective learning style-critical students of different faculties of the University of Engineering was high and medium, and (3) regarding the correlation between the level of intrinsic motivation and level of development learning style-critical reflective found a significant relationship. So we may conclude in this study sample that there are significant relationships between the intrinsic motivation and the learning style, critical reflective college students at the Universidad Nacional de Ingeniería.